2013
DOI: 10.3724/sp.j.1123.2011.08055
|View full text |Cite
|
Sign up to set email alerts
|

Determination of glyoxalate and oxalate by capillary zone electrophoresis

Abstract: A method for the simultaneous determination of glyoxalate and oxalate by capillary zone electrophoresis (CZE) was developed. The influences of type, concentration and pH of the running buffer, and the applied voltage on separation were investigated. Glyoxalate and oxalate were separated within 11 min under the conditions of 20 mmol/L borax-5.5 mmol/L potassium hydrogen phthalate (pH 9.0), applied voltage of 20 kV, and detected wavelength of 212 nm. The calibration curves of glyoxalate and oxalate showed good l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…When some of the past studies based on the analysis of similar matrices in the literature were considered in Table 5, a good sensitivity improvement and extraction efficiency, in terms of detection limit (LODs) and preconcentration and enhancement factors (PF and EF), were achieved by the proposed method according to those of different separation and detection techniques like DPP (Rodrigues and Barros 1993), CZE on a chip with conductivity detection (Masar et al 2003), CZE (Guan et al 2012), catalytic spectrophotometry (Safavi and Banazadeh 2007), HPLC with chemiluminescence detection (Wu et al 1999), HPLC-ER (Hönow et al 1997), ion suppression RP-HPLC (Lian et al 1999), HPLC (Judprasong et al 2006), HS-GC (Li et al 2014), enzymatic assays using oxalate oxidase (Kasidas and Rose 1980), and IC (Holmes and Kennedy 2000) without preconcentration. The detection limits, LODs (0.36 μg L −1 ), obtained in the present study are either better than or comparable to those of the reported The present study detection methods.…”
Section: Comparison Of the Proposed Methods With Other Preconcentratiomentioning
confidence: 99%
See 1 more Smart Citation
“…When some of the past studies based on the analysis of similar matrices in the literature were considered in Table 5, a good sensitivity improvement and extraction efficiency, in terms of detection limit (LODs) and preconcentration and enhancement factors (PF and EF), were achieved by the proposed method according to those of different separation and detection techniques like DPP (Rodrigues and Barros 1993), CZE on a chip with conductivity detection (Masar et al 2003), CZE (Guan et al 2012), catalytic spectrophotometry (Safavi and Banazadeh 2007), HPLC with chemiluminescence detection (Wu et al 1999), HPLC-ER (Hönow et al 1997), ion suppression RP-HPLC (Lian et al 1999), HPLC (Judprasong et al 2006), HS-GC (Li et al 2014), enzymatic assays using oxalate oxidase (Kasidas and Rose 1980), and IC (Holmes and Kennedy 2000) without preconcentration. The detection limits, LODs (0.36 μg L −1 ), obtained in the present study are either better than or comparable to those of the reported The present study detection methods.…”
Section: Comparison Of the Proposed Methods With Other Preconcentratiomentioning
confidence: 99%
“…The determination methods of oxalate species are mainly based on flow injection spectrofluorimetric determination (FISD) (Pérez-Ruiz et al 1995), gas chromatography-mass s p e c t r o m e t r y ( G C -M S ) ( M a r c h e t a l . 2 0 0 3 ) , spectrofluorimetry (Cha et al 2002), amperometry (Pundir et al 2011), chemiluminescence (Pérez-Ruiz et al 2005), ion chromatography (IC) with chemiluminescence detection (Maya et al 2011), high-performance liquid chromatography (HPLC) (Hönow and Hesse 2002;Judprasong et al 2006), linear sweep voltammetry (LSV) (Šljukić et al 2007), differential pulse polarography after derivatization with ophenylenediamine (DPP) (Rodrigues and Barros 1993), capillary zone electrophoresis (CZE) on a chip with conductivity detection (Masar et al 2003), CZE (Guan et al 2012), HPLC (Judprasong et al 2006), headspace gas chromatography (HS-GC) (Li et al 2014), catalytic spectrophotometry (Safavi and Banazadeh 2007), HPLC with chemiluminescence detection (Wu et al 1999), HPLC-ER (Hönow et al 1997), ion suppression RP-HPLC (Lian et al 1999), enzymatic assays using oxalate oxidase (Kasidas and Rose 1980), capillary electrophoresis (CE) and ion chromatography (IC) (Holmes and Kennedy 2000), and ion-exchange high-performance liquid chromatography (IE-HPLC) (Nguyễn and Savage 2013) until now. Determination of oxalate via these methods such as GC-MS and flow injection spectrofluorimetry that have very high analytical sensitivity is expensive and time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are mainly based on enzymatic analysis with arylamine bound oxalate oxidase and peroxidase [6], spectrochemical [7,8], electrochemical [9,10] and chromatographic separations [11][12][13][14][15][16][17][18][19][20][21]. Determination of oxalate by the sensitive methods such as GC-MS, LC-MS, CE-MS and flow injection spectrofluorimetry are expensive and time consuming.…”
Section: Introductionmentioning
confidence: 99%